Decreto del Sumo Pontífice Francisco relativo a Caritas Internationalis (22-11-2022): Texto y comentario. - Prisco, José San José (Revista española de derecho canónico, 2022)
Original text in Italian and commentary on the Pope's document on the intervention of Caritas international